Off-pump bidirectional Glenn through right anterior thoracotomy - Maximo Guida; Andrea Lo Cascio; Gustavo Guida; Gabriel Guida; Estefania De Garate; Manuel Vasquez; Fernando Prieto; Miriam Pecchinenda (Brazilian Journal of Cardiovascular Surgery, 2015)
Abstract The Glenn operation involving anastomosis of the superior vena cava to the pulmonary artery has been performed for palliative operations of many cyanotic congenital heart diseases in addition to the single ventricle since the 1960s. The classic procedure is done via median sternotomy and cardiopulmonary bypass. The benefits of this procedure without the use of cardiopulmonary bypass remain mixed within reported series. Cases using this approach and off-pump technique together in Latin-America have not yet been reported in the scientific literature.